PENGARUH PENDEKATAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) BERBASIS YOUTUBE TERHADAP KETERAMPILAN MENYIMAK DONGENG - Aulia Mahgfira Cahyani; Sitti Aida Azis; Andi Paida (Jurnal Pendidikan Sang Surya, 2024)
The main problem in this research is that students are less focused on listening learning because the teacher has not used inappropriate learning media, learning media is only displayed in the classroom so that students' interest and motivation for listening learning is lacking and makes the learning outcomes obtained by students low. his research aims to determine the effect of the YouTube-based Technological Pedagogical Content Knowledge (TPACK) approach on fairy tale listening skills in fifth grade students at SD Negeri Manjalling, West Bajeng District, Gowa Regency. The type of research used in this research is experimental research, especially pre-experimental and is a quantitative type of research. The sample in this study was 22 students. The data collection techniques used by researchers are observation, tests and documentation. The data analysis techniques in this research are descriptive statistical analysis and inferential statistical analysis. The research results show that the skill of listening to fairy tales before implementing the YouTube-based Technological Pedagogical Content Knowledge (TPACK) approach in the pretest with an average score of 52,7. Meanwhile, the posttest increased with an average score of 84,5. The results of the t-test analysis regarding the influence of the YouTube-based Technological Pedagogical Content Knowledge (TPACK) approach on the learning outcomes of student participants show that the significance value obtained is good, namely the influence of the YouTube-based Technological Pedagogical Content Knowledge (TPACK) approach on fairy tale listening skills (Sig = 0.001 ) is smaller than the set alpha value, namely 0.001 < 0.05. Based on the results obtained, it can be concluded that Ho is rejected and H1 is accepted, which states that there is an influence of the YouTube-based Technological Pedagogical Content Knowledge (TPACK) approach on the fairy tale listening skills of class V students at SD Negeri Manjalling, West Bajeng District, Gowa Regency.